Solitary intramuscular cysticercosis: A rare pseudotumour. A report of two cases - Marasini, R P; Thapa, P B; Gautam, P (Journal of Chitwan Medical College, 2015)
Cysticercosis is a disease caused by cysticercus cellulosae, a larval form of tapeworm, Taenia solium. Solitary muscular involvement is a rare and often presents diagnostic challenges due to unusual clinical presentation. Conventionally these conditions are diagnosed by histopathology or MR imaging and treated by surgical excision followed by antihelminthetic medication. We reported 2 cases of solitary intramuscular cysticercosis (biceps brachii and soleus muscle) without any systemic and neurological manifestations, accurately diagnosed by ultrasonogrphy and successfully treated conservatively with antihelminthetics and steroids.